Relações de aminoácidos sulfurados: lisina digestíveis e diferentes fontes de betaína nas dietas pré-inicial e inicial de frangos - Rezende, Pedro Moraes (2015)
Researches with the use of betaine in broiler diets have shown its role inintestinal osmoregulator under stress, increasing cell water retention and its role as a methyl group donor in metabolic processes.The use of additives as betaine is a good economical alternative to feed chickens. The objective of this study was to evaluate growing relations of sulfur amino acids: lysine in combination with two sources of betaine in broiler diet in pre-starter and starter phases.The experiment was conducted at experimental poultry of School Veterinary and Animal Science of Federal University of Goiás in Goiânia, The experimental protocol was approved by the Ethics Committee on Animal Use / CEUA registered under protocol. 068/13. 504 chicks Cobb 500® males with a day old were housed, in galvanized steel batteries with five floors, troughs and linear feeders Division and incandescent lamps for heating.The experimental designused was randomized block in a 3x4 factorial design, corresponding to diets containing betaine (synthetic and natural) compared to the control with out use of the compound, and different relations of methionine+cystine: digestible lysine (57%, 65%, 73% and 81%), with 12 treatments, 6 replicates of 7 birds.The experimental diets of corn and soybean meal, free from growth promoters and anticoccidial, were formulated with the exception of methionine and cystine levels in the appropriate treatments, and the DLmethionine added to replace the starch. Performance was measured with the weighing of birds and diets on the accommodation and 7, 14 and 21 days of age, determining the average final weight, weight gain, feed intake and feed conversion, For the blood biochemical profile, blood was collected for determination of serum Na+, K+, Cl-, albumin, globulin, albumin:globulin, protein, cholesterol, triglycerides, HDL, VLDL, LDL and uric acid. Formetabolizability of nutrients was used the total excreta collection 4-7 days and 17-21 days of age, determining the coefficients of raw dry, nitrogen and nitrogen retained and nitrogen balance. Necropsies were done on chicks with 7 and 21 days of age, during which time samples were collected from the small intestine (duodenum, jejunum and ileum) for mounting histological slides and weighing the organs of the gastrointestinal tract (GIT). For histomorphometry, was checked villus height, crypt depth and villous:crypt duodenum, jejunum and ileum. Data were subjected to analysis of variance (P <0,10) and applied to polynomial regression analysis for methionine+ cystine: lysine. Al though there was no expressive difference in the use of betaine sources, you can check the sparing effect of methionine, as the birds fed the lower methionine+ cystine: lysine showed higher weights when supplemented with betaine, in particular the source of natural betaine. There was a positive interaction of betaine on the Met+Cys relations: Lys digestible for blood biochemistry profile, villus height and metabolization of nutrients.